2018
DOI: 10.12659/msm.908545
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Studies of Noncalcified Nodules Related to Neuroendocrine Lung Tumor Using 68Gallium-Tagged Somatostatin Variant for Improvement in Diagnosis: A Non-Experimental, Non-Randomized, Cross-Sectional Study

Abstract: Background18Fluoro-fluorodeoxyglucose (FDG)- based positron-emission computed tomography (PET) has less specificity for noncalcified nodules (NNs). Somatostatin receptors affect the expression of normal and malignant cells. The purpose of the study was to compare the sensitivity, specificity, and accuracy of 68Gallium-tagged DOTA-octreotate (Ga-tDO) with that of FDG PET for diagnosis of newly detected and/or untreated NNs in lung cancer patients.Material/MethodsA total of 45 patients with lung cancer were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Li et al . [ 39 ] found that in a group of NSCLC patients 68 Ga-DOTA-TATE is more specific than FDG and accuracy between the two radiopharmaceuticals does not show significant differences.…”
Section: Pet Imaging In Pulmonary Nensmentioning
confidence: 99%
“…Li et al . [ 39 ] found that in a group of NSCLC patients 68 Ga-DOTA-TATE is more specific than FDG and accuracy between the two radiopharmaceuticals does not show significant differences.…”
Section: Pet Imaging In Pulmonary Nensmentioning
confidence: 99%